Determinants of Effective Financial Management in Regional Public Service Agencies at State Vocational High Schools in Bengkulu Province - Asnawati; Sudarwan Danim (The Indonesian Institute of Science and Technology Research, 2026)
This study investigates the determinants of financial management effectiveness of Regional Public Service Agencies (BLUD) at State Vocational High Schools in Bengkulu Province, Indonesia. A causal-quantitative approach was employed, with data collected from 56 respondents across eight BLUD-designated State Vocational High Schools through purposive sampling. Four independent variables were examined: information technology (IT) utilization, human resource (HR) competency, governance, and functional supervision. Data was collected via a five-point Likert-scale questionnaire and analyzed using multiple linear regression. Results show that IT utilization (β = 0,422, p = 0,037), HR competency (β = 0,890, p = 0,000), and governance (β = 0,761, p = 0,023) each exerted a positive and significant effect on BLUD financial management effectiveness, while functional supervision yielded no significant effect (β = 0,017, p = 0,920). The overall model was statistically significant (F = 25,341, p = 0,000, Adjusted R² = 62,7%). These findings indicate that internal organizational factors, particularly HR competency, IT infrastructure, and governance structures, are far more decisive determinants of BLUD financial management effectiveness than formal external oversight mechanisms. The study contributes to the scarce empirical literature on BLUD financial management in vocational education and provides actionable policy recommendations for strengthening public-sector financial governance in regional Indonesia.